2023
DOI: 10.3390/microorganisms11041006
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Silver Nanoparticles Produced by Soil Rare Actinomycetes and Their Significant Effect on Aspergillus-derived mycotoxins

Abstract: The current investigation addressed the green synthesis of silver nanoparticles (AgNPs) using newly isolated silver-resistant rare actinomycetes, Glutamicibacter nicotianae SNPRA1 and Leucobacter aridicollis SNPRA2, and investigated their impact on the mycotoxigenic fungi Aspergillus flavus ATCC 11498 and Aspergillus ochraceus ATCC 60532. The formation of AgNPs was evidenced by the reaction’s color change to brownish and the appearance of the characteristic surface plasmon resonance. The transmission electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…Singh et al 42 found that 15 isolates have antibacterial activity against Gram‐positive bacteria and MDR bacteria by the perpendicular streak method. Ghany et al, 38 discovered that actinomycete‐mediated silver nanoparticles could disrupts the life cycle of mycotoxigenic fungi, inhibiting conidial germination and compromising membrane integrity, leading to reduced aflatoxin and ochratoxin A production. The metabolite production by submerged state fermentation techniques shows good results in antimicrobial activity 43 against pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Singh et al 42 found that 15 isolates have antibacterial activity against Gram‐positive bacteria and MDR bacteria by the perpendicular streak method. Ghany et al, 38 discovered that actinomycete‐mediated silver nanoparticles could disrupts the life cycle of mycotoxigenic fungi, inhibiting conidial germination and compromising membrane integrity, leading to reduced aflatoxin and ochratoxin A production. The metabolite production by submerged state fermentation techniques shows good results in antimicrobial activity 43 against pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The isolates LA2(R) M. proteolyticum and LA2(O) S. rochei were inoculated in a 500 mL flask containing 100 mL of ISP‐2 medium (g/L): yeast extract, 4.0; malt extract, 10.0; dextrose, 4.0; agar, 20.0; distilled water, 1000 mL; and pH, 7.3. The flasks with inoculated strains were incubated for 5–7 days at 200 rpm in a rotary shaker 38 . The cultures were centrifuged at 10,000 rpm after the growth, and its supernatant was used for future experimentations 39 …”
Section: Methodsmentioning
confidence: 99%
“…Recently, Ghany et al synthesized monodispersed spherical AgNPs having an average size of 8.48 ± 1.72 nm and 9.67 ± 2.64 nm from actinomycetes Glutamicibacter nicotianae SNPRA1 and Leucobacter aridicollis SNPRA2, respectively [ 90 ]. Further, Nayka and their team also reported the formation of spherical and polydisperse AgNPs of size 32.40 nm from Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%